64 | ( | 1 | + | x | ) | ( | 1 | + | x | ) | = | 100 |
Left side of the equation = | 64 | × | 1 | ( | 1 | + | x | ) | + | 64 | x | ( | 1 | + | x | ) |
= | 64 | ( | 1 | + | x | ) | + | 64 | x | ( | 1 | + | x | ) |
= | 64 | × | 1 | + | 64 | x | + | 64 | x | ( | 1 | + | x | ) |
= | 64 | + | 64 | x | + | 64 | x | ( | 1 | + | x | ) |
= | 64 | + | 64 | x | + | 64 | x | × | 1 | + | 64 | x | x |
= | 64 | + | 64 | x | + | 64 | x | + | 64 | x | x |
= | 64 | + | 128 | x | + | 64 | x | x |
64 | + | 128 | x | + | 64 | x | x | = | 100 |
x1= | - | 9 4 |
x2= | 1 4 |